The geology of a portion of south-western Albany - Meyer, W (Rhodes University, Faculty of Science, Department of Geology, 1965)
During 1963 an area was mapped around Sidbury, 23 miles south- west of Grahamstown. The object of the survey was to examine stratigraphic problems, which included the nature of a large occurrence of shale south of Alicedale in a region previously mapped as Witteberg, and the relationship between Silcrete and Calcrete. During the invest igation evidence of the existence of two, possibly three , major thrust-faults and of extensive overfolding to the south was discovered. There is reason to believe, that movement on the Zuurberg Fault was initiated in pre-Cretaceous times, and renewed in the early Cretaceous. The Silcrete is shown to be related to the pattern of presentday drainage. Stone implements found embedded in the Calcrete suggest that it is of Recent age.
Keywords: Geology -- South Africa -- Eastern Cape; Silcrete; Geology, Stratigraphic